2018
DOI: 10.1371/journal.pone.0196722
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal colonization and drug resistance profiles of Morraxella catarrrhalis, Streptococcus pneumoniae, Staphylococcus aureus, and Haemophilus influenzae among HIV infected children attending ART Clinic of Felegehiwot Referral Hospital, Ethiopia

Abstract: BackgroundAsymptomatic pharyngeal colonization by potential bacteria is the primary reservoir for bacterial species within a population and is considered a prerequisite for development of major childhood diseases such as sinusitis, otitis media, pneumonia, bacteremia, and meningitis. However, there is dearth of data on the colonization and drug resistance pattern of the main bacterial pathogens in the pharynx of HIV infected children in Ethiopia. Therefore, this study determined the pharyngeal colonization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
26
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 41 publications
9
26
5
Order By: Relevance
“…On the other hand, our findings showed the emergence of resistance to trimethoprim-sulfamethoxazole (14.7%), and ciprofloxacin (2.9%). Various previous studies conducted globally reported the spread of resistance to trime thoprim-sulfamethoxazole among M. catarrhalis isolates, such as 12.5% in Tunisia [21], 13.8% in Australia [22] [20], and 100% in Iran [25]. Based on the aforementioned data, the spread of cotrimoxazole resistance among M. catarrhalis isolates in developing countries is shocking, and reveals a prominent threat jeopardizing the clinical efficacy of this important antibiotic.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, our findings showed the emergence of resistance to trimethoprim-sulfamethoxazole (14.7%), and ciprofloxacin (2.9%). Various previous studies conducted globally reported the spread of resistance to trime thoprim-sulfamethoxazole among M. catarrhalis isolates, such as 12.5% in Tunisia [21], 13.8% in Australia [22] [20], and 100% in Iran [25]. Based on the aforementioned data, the spread of cotrimoxazole resistance among M. catarrhalis isolates in developing countries is shocking, and reveals a prominent threat jeopardizing the clinical efficacy of this important antibiotic.…”
Section: Discussionmentioning
confidence: 97%
“…Regrettably, tetracycline resistance has emerged in numerous developing and developed countries. The higher levels of resistance were reported in China [19], Taiwan [2] and Ethiopia [20]. Furthermore, several studies realized in developing countries indicated unexpected levels of antimicrobial resistance to erythromycin in M. ca-tarrhalis isolates, with 59.1% in Pakistan [13], 70.8% in China [19], and 86.6% in Ethiopia [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data are consistent with the ancient Chinese saying and the view of international scientists [7]: boys are more easily to be infected compared with girls. [9]. The related papers have reported that the separation rate is much higher for children than the adults [10].…”
Section: The Comparison Between Different Gendersmentioning
confidence: 99%
“…This may affect children's immune function which is not fully mature, and can easily acquire acute upper respiratory tract infection. Respiratory pathogens in nasopharynx is closely related to factors such as the number of carrying rate and engraftment [9,10].…”
Section: The Comparison Between Different Gendersmentioning
confidence: 99%